The efficacy of online shaming as a modality for social control / Haswira Nor Mohamad Hashim, Anida Mahmood and Nurul Shuhada Suhaimi - Mohamad Hashim, Haswira Nor; Mahmood, Anida; Suhaimi, Nurul Shuhada (Universiti Teknologi MARA, Kedah, 2018)
37 This paper examines the efficacy of online shaming as a modality for social control. Social control is the process of regulating individual or group behaviour, to encourage conformity and obedience. A survey amongst 320 UiTM law students was conducted. A self-developed survey questionnaire with five point-Likert scale was used for data collection. A cross-sectional survey was conducted on the survey population. The findings of the survey provide an insight on the efficacy of online shaming as a modality for social control. The research provides a beneficial input on the worthiness of considering online shaming as formal sanction. The survey reveals that online shaming has been used as a platform to shame, to exact revenge, to intimidate and to condemn people or wrongdoers. The efficacy of online shaming as a modality for social control is answered in negative, thus not suitable to be regulated as a formal sanction.